Penggunaan Bahasa Indonesia Warga Sekitar Yang Dapat Berpengaruh Dalam Lingkungan Sosial Dan Budaya - Basyirotul Hilmi; Hildhan Reicky Saputra; Sulis Safaatin Hidayah; Romy Trizki Suwardana; Yosafat Prayoga Purba W (CV. Alim's Publishing, 2023)
The use of Indonesian can affect the distribution of power among local residents, either through the choice of words or phrases used, the style of communication, or access to information. The use of Indonesian by local residents also has implications for community empowerment and involvement. When people have broad access and a good understanding of Indonesian, they can participate actively in life. The use of Indonesian by local residents can also have an impact on cultural sustainability and create social harmony. Indonesian is stipulated in the 1945 Constitution and Indonesian has been studied in several countries. But that does not mean, the existence of the Indonesian language does not experience problems. Slang appears because of the dynamics in people's lives. The diversity of local cultures and languages ​​has a role and influence on the Indonesian language. It cannot be denied that cultural and linguistic diversity is the uniqueness of the Indonesian nation and a wealth that must be preserved. But this diversity affects Indonesian as the language of unity.